Meningkatkan Hasil Belajar Matematika pada Materi Bangun Datar melalui Model Pembelajaran Teams Games Tournament - Khalimah, Siti Nur (Universitas Muhammadiyah Magelang, 2018)
This study aims to improve students mathematics learning outcomes in the material wake up flat through the learning model Team Games Tournament in grade 2 students SDN Majaksingi Borobudur. The study design uses Class Action Research with II cycle where each cycle consists of 2 meetings. The subjects of the study were class II of 26 students. The population of this research is 26 students. The sampling technique used is total sampling. research variables using 2 variables that are learning outcomes Mathematics and learning model Team Games Tournament. Methods of data collection using tests and observations. Data analysis used is descriptive percentage. The results showed, TGT learning model can improve learning Mathematics about wake flat. This is evidenced by data from the initial condition until cycle II. In the initial condition the percentage of students completeness reached 61.53% and in cycle II, the percentage of students mastery reach 88.46%.